Bargaining River Lords: Lordship and Spatial Politics in Premodern Guelders (Fifteenth-Sixteenth Centuries - Van der Meulen, Jim (TSEG - The Low Countries Journal of Social and Economic History, 2021)
This article offers an examination of the seigneurie (heerlijkheid) as an element in the institutional framework of Netherlandish water management. The investigation builds on a recent historiographical trend that questions whether inclusive systems of water management can be tied to ‘proto-democratic’ decision-making in the premodern Low Countries. Focusing on the fifteenth- and sixteenth-century river region of the duchy of Guelders, the central question is to what extent lords, ladies, and their seigneurial officials impacted the natural environment of people living in rural regions. Based on a combination of seigneurial accounts and court records, the main thesis is that the aristocratic element formed an ambiguous yet important cog in the late medieval system of water management in Guelders.